RELEVANSI BUDAYA MELAYU DALAM CERITA “SENANDUNG DAYANG DERMA” - Sri Sabakti (Madah: Jurnal Bahasa dan Sastra, 2017)
The drama script “Senandung Dayang Derma” (SDD) (Dayang Derma Humming) written by Rina Nazaruddin is a story that close to Malay culture. The analysis of SDD story will be carried out by using literary anthropology and literary sociology approach. Literary anthropology approach is applied to analyze cultural elements in the story, whereas literary sociology approach is applied to analyze social fact, i.e. habits, norms and customs that exist in Riau Malay community. The method used is descriptive analysis method. Descriptive-analytical methods are used to describe, comprehend, and explain the cultural elements in literary works and then followed by analyzing. The result of analysis shows that cultural elements, i.e. language and social system in SDD story have relevance to the culture of Riau Malay Community.